Non-enzymatic lactose molecularly imprinted sensor based on disposable graphite paper electrode - da Silva, José Luiz [UNESP]; Buffon, Edervaldo [UNESP]; Beluomini, Maísa Azevedo [UNESP]; Pradela-Filho, Lauro Antonio; Gouveia Araújo, Diele Aparecida; Santos, André Luiz; Takeuchi, Regina Massako; Stradiotto, Nelson Ramos [UNESP] (Elsevier, 2021)
Lactose (LAC) is a disaccharide - major sugar, present in milk and dairy products. LAC content is an important indicator of milk quality and abnormalities in food industries, as well as in human and animal health. The present study reports the development of an innovative imprinted voltammetric sensor for sensitive detection of LAC. The sensor was constructed using electropolymerized pyrrole (Py) molecularly imprinted polymer (MIP) on graphite paper electrode (PE). The MIP film was constructed through the electrosynthesis of polypyrrole (PPy) in the presence of LAC (template molecule) on PE (PPy/PE). To optimize the detection conditions, several factors affecting the PPy/PE sensor performance were assessed by multivariate methods (Plackett–Burman design and central composite design). Under optimized conditions, the proposed analytical method was applied for LAC detection in whole and LAC-free milks, where it demonstrated high sensitivity and selectivity, with two dynamic linear ranges of concentration (1.0–10 nmol L−1 and 25–125 nmol L−1) and a detection limit of 0.88 nmol L−1. The MIP sensor showed selective molecular recognition for LAC in the presence of structurally related molecules. The proposed PPy/PE sensor exhibited good stability, as well as excellent reproducibility and repeatability. Based on the results obtained, the PPy/PE is found to be highly promising for sensitive detection of LAC.
Keywords: Electropolymerization; Experimental design; Lactose sensing; Molecularly imprinted polymers; Non-enzymatic electroanalysis; Paper-based electrode